Bt rice producing Cry1C protein does not have direct detrimental effects on the green lacewing Chrysoperla sinica (Tjeder). (22nd April 2014) - Li, Yunhe; Chen, Xiuping; Hu, Long; Romeis, Jörg; Peng, Yufa
Abstract The effects of insect‐resistant genetically engineered rice producing Cry1C protein derived from Bacillus thuringiensis (Bt) on Chrysoperla sinica (Tjeder) (Neuroptera: Chrysopidae) were assessed in laboratory bioassays. Survival and development of C. sinica larvae were not adversely affected when the larvae were fed a diet containing purified Cry1C protein at 200 µg/g fresh weight, representing a worst‐case exposure scenario; in contrast, C. sinica larvae were adversely affected when the diet contained avidin or potassium arsenate. Life table parameters of C. sinica adults did not differ when the adults were fed with Bt or non‐Bt rice pollen together with a 2‐M sucrose solution. Life table parameters of C. sinica adults also did not differ when the adults were fed an artificial diet with or without purified Cry1C protein at a nominal concentration that was approximately 20 times higher than that in rice pollen; in contrast, C. sinica adults were adversely affected when the diet contained potassium arsenate. In all bioassays with lacewings, the bioactivity and stability of the Cry1C protein in the diet and Cry1C protein uptake by the lacewings were confirmed by enzyme‐linked immunosorbent assay (ELISA) and by bioassays with a Cry1C‐sensitive lepidopteran. These results demonstrate that neither larvae nor adults of C. sinica are sensitive to Cry1C protein at concentrations higher than those encountered in the field, demonstrating that the growing of Bt rice producing Cry1C protein is unlikely to pose a risk to C. sinica. Environ Toxicol Chem 2014;33:1391–1397. © 2014 SETAC